The effects of seasonality and precipitation in the avifauna of the Argentine Southern Chaco Serrano - Fava, Gustavo Alfredo; Acosta, Juan Carlos; Blanco, Graciela Mirta (Revista de Biología Tropical, 2017)
In subtropical regions like the Chaco Serrano (33° S), rainfall has a marked seasonality, and water flood, caused by heavy rains, may have important consequences for dependent ecosystems. Conversely, the high pressure on available resources during dry periods can also affect the fauna diversity and distribution. Even though birds have shown to be excellent ecological indicators of these shifts in the environment, currently little is known about the avifauna of the Argentine Chaco Serrano phytogeographic district. Our aim was to study the resident bird population status in the Southern Chaco Serrano, its fluctuations in richness and abundance, and its relationship to seasonal variations, in monthly and annual hydroperiods. In order to assess the resident bird status over a two year period (2011 Mar.-2013 Feb.) we carried out 18 sampling surveys during pre-breeding (spring), breeding (summer) and non breeding periods (autumn-winter), in the Northeastern part of the Valle Fértil Natural Park, San Juan province, Argentina. During each site survey, we recorded bird assemblages found in six transects, and obtained bird abundance and species diversity. A mixed general linear model was employed to evaluate relationships between the studied variables. We found a total of 98 species of birds belonging to 33 families (44 resident species, 23 spring visitors, six summer visitors, two winter visitors and 23 with scarce registers). We also registered 68 of these species in both hydroperiods, 28 only during rainy periods and only two during the dry period. Both richness and abundance showed the highest values during the pre-breeding and rainy seasons, while different tendencies were detected during the isolated monthly rainfalls. These changes in bird densities were associated with the arrival of migratory species, mainly spring visitors, and probably in relationship with their reproductive activity, and to seasonal fluctuations in food resources. The Southern Chaco Serrano is a subtropical semiarid place that seems to be an important breeding habitat for many migrant bird species, which in turn promoted seasonal changes in species density and diversity, mainly during rainy years. This work contributed to our understanding on the causes of richness and abundance variations on birds, and will contribute to this important group management and conservation in this area.